The ethical chemist professionalism and ethics in science - Kovac, Jeffrey (Oxford University Press, 2018)
"This book is an introduction to professional ethics in chemistry based on the view that the specific codes of conduct derive from a moral ideal. Ethical questions unique to chemistry are discussed. A large collection of specific ethical problems are included."...